PERAN POTENSIAL BIOMARKER MOLEKULER DALAM MENILAI EFEKTIVITAS KLINIS INTERVENSI PROBIOTIK PADA PENYAKIT SALURAN PENCERNAAN - Gasela Zalianti Balqis; Jesika Cahya Ningrum; Giska Tri Putri; Maya Ganda Ratna (Nusantara Hasana Journal, 2026)
Gastrointestinal diseases represent a significant global health burden and require complex management. Current assessments of probiotic efficacy often rely on subjective patient reports, which can be potentially biased. This review aims to explore the potential of molecular biomarkers to provide objective measures of therapeutic response. A narrative review was conducted through PubMed, Google Scholar, and Cochrane databases. The literature was screened using the PICO framework, focusing on gastrointestinal diseases, probiotic interventions, and molecular biomarker outcomes. Probiotic therapy effectively modulates the gut-brain axis and restores microbiota homeostasis. Specific biomarkers such as fecal calprotectin (inflammation), malondialdehyde (oxidative stress), and zonulin and occludin (barrier integrity) have been shown to be robust indicators for patient monitoring. Changes in these biomarkers significantly correlate with improvements in clinical symptoms, such as pain reduction and normalization of stool consistency. The integration of molecular biomarkers provides an objective, evidence-based framework for evaluating the efficacy of probiotic therapy, supporting the transition to precision medicine in gastroenterology.